Construções comparativas em português: porque algumas são mais iguais que outras. - Pereira, Sandra (2014)
In Portuguese comparative constructions of inequality, either do que or que may be the syntactic heads of the Degree Clause. There are, however, differences in their distribution: do que is allowed in all contexts, whereas que is barred whenever the Degree Clause includes a finite verb phonologically realized. In the present paper we claim that all canonical comparative constructions in European Portuguese include two full clauses and that, whenever some constituents of the Degree Clause are phonologically null, what we have is a case of ellipsis, whose extent is different for do que and que.